2008
DOI: 10.1016/j.neuropharm.2008.08.034
|View full text |Cite
|
Sign up to set email alerts
|

How the serotonin story is being rewritten by new gene-based discoveries principally related to SLC6A4, the serotonin transporter gene, which functions to influence all cellular serotonin systems

Abstract: Discovered and crystallized over sixty years ago, serotonin's important functions in the brain and body were identified over the ensuing years by neurochemical, physiological and pharmacological investigations. This 2008 M. Rapport Memorial Serotonin Review focuses on some of the most recent discoveries in serotonin that are based on genetic methodologies. These include examples of the consequences that result from direct serotonergic gene manipulation (gene deletion or overexpression) in mice and other specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
183
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(189 citation statements)
references
References 285 publications
(534 reference statements)
6
183
0
Order By: Relevance
“…5-HTT encodes for a protein involved in serotonin re-uptake. Studies of this gene in non-human primates and in human populations have identified a promoter-linked polymorphic region that interacts with early experience to affect behaviours in the young and adults [23]. The long and short alleles result from a 43 bp insertion/deletion in the promoter region of the 5-HTT gene.…”
Section: Case Studies In the Conservation Of Gene Function In Behaviourmentioning
confidence: 99%
“…5-HTT encodes for a protein involved in serotonin re-uptake. Studies of this gene in non-human primates and in human populations have identified a promoter-linked polymorphic region that interacts with early experience to affect behaviours in the young and adults [23]. The long and short alleles result from a 43 bp insertion/deletion in the promoter region of the 5-HTT gene.…”
Section: Case Studies In the Conservation Of Gene Function In Behaviourmentioning
confidence: 99%
“…The serotonin transporter SERT or 5-HTT, encoded by the SLC6A4 gene, is thought to play a prominent role in serotonin homeostasis in primates and non-human primates, and several gene variants that may change the structure or function of the transporter protein were associated with autism [8]. Among them, polymorphisms within the 5-HTTLPR promoter sequence, mutations in the coding sequence, or intronic mutations of this serotonin transporter were reported to be linked to autism by some studies, but other studies have been inconclusive [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, polymorphisms within the 5-HTTLPR promoter sequence, mutations in the coding sequence, or intronic mutations of this serotonin transporter were reported to be linked to autism by some studies, but other studies have been inconclusive [8][9][10]. The SLC6A4 5-HTTLPR promoter sequence, located about 1 kb upstream of the transcription initiation site, contains two variable repeat length polymorphisms known as the long (L) with 16 repeat elements, or the 44 bp shorter (S) variant with 14 repeat elements [11,12], which determines a different expression of the serotonin transporter in pre-synaptic axonic membranes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparison between the S-[short] and L-[long] alleles of 5-HTTLPR shows that the L-allele exerts increased transcriptional activity and increased basal reuptake of serotonin in vitro Lesch et al 1996;Murphy et al 2008). The L-allele is, therefore, referred to as the gain-of-function variant of the serotonin transporter.…”
mentioning
confidence: 99%